A Review of the Role of Natural Products as Treatment Approaches for Xerostomia - Konstantinos N. Kontogiannopoulos; Afroditi Kapourani; Ioannis Gkougkourelas; Maria-Emmanouela Anagnostaki; Lazaros Tsalikis; Andreana N. Assimopoulou; Panagiotis Barmpalexis (MDPI AG, 2023)
Xerostomia, commonly known as dry mouth, is a widespread oral health malfunction characterized by decreased salivary flow. This condition results in discomfort, impaired speech and mastication, dysphagia, heightened susceptibility to oral infections, and ultimately, a diminished oral health-related quality of life. The etiology of xerostomia is multifaceted, with primary causes encompassing the use of xerostomic medications, radiation therapy to the head and neck, and systemic diseases such as Sjögren's syndrome. Consequently, there is a growing interest in devising management strategies to address this oral health issue, which presents significant challenges due to the intricate nature of saliva. Historically, natural products have served medicinal purposes, and in contemporary pharmaceutical research and development, they continue to play a crucial role, including the treatment of xerostomia. In this context, the present review aims to provide an overview of the current state of knowledge regarding natural compounds and extracts for xerostomia treatment, paving the way for developing novel therapeutic strategies for this common oral health issue.